La Teología como ciencia según Enrique de Gante - Brandariz, Francisco (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 1948)
The author's approach to the so-called "theological problem", that is, to the problem about the very essence of theological science, which is carried out by the figure of Henry of Ghent, mainly, for four reasons: the time in which he develops his scientific activity, his personality, the absence of modern works about his theological thought and, finally, the intrinsic value of his Introduction to the Summa, the most suitable to focus a study of Theology as a science in his time.
Keywords: Henry of Ghent; theological problem; Introduction to the Summa; theological subject; purpose of theology; theocentric